Comparison of selective harmonic elimination and SPWM techniques for unipolar inverters - Hassan E. Aboadla, Ezzidin; Khan, Sheroz; H. Habaebi, Mohamed; Gunawan, Teddy; Hamidah, Belal; Bin Yaacob, Mashkuri; Aboadla, Ali (International Journal of Engineering and Technology, 2019)
Several modulation schemes are used to operate power electronics devices MOSFETs and IGBTs in power converters and are also utilized to reduce the influence of Total Harmonic Distortion (THD) in the output voltage of these inverters. Selective Harmonic Elimination (SHE) and Sinusoidal Pulse Width Modulation (SPWM) are the most popular techniques used in this regard. Number of notches and modulation index (m) are the important parameters used to design both techniques. Total Harmonic Distortion is utilized as a standard to measure the signal quality for both schemes. This paper discusses a comparison study of using SHE and SPWM techniques in full bridge inverter. MATLAB and PSIM tools are used to estimate and verify the performance of both techniques and the results are obtained experimentally.Â Â